Perilaku Bisnis Beretika : Strategi Menghadapi Persaingan Secara Professional - Moch Iqbal Romadhon; Dicky Satria Ananta Haqq; Tries Ellia Sandari (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Ethical business conduct is increasingly considered important as a strategy to face competition professionally in the era of globalization and digitalization. Business ethics help companies build strong trust, reputation and loyalty among customers, employees and other stakeholders. This research explores various forms of ethical behavior in business, including transparency, social responsibility, and commitment to fair and sustainable practices. Through theoretical approaches and case studies, this research shows that companies that adopt ethical behavior not only improve their image in the eyes of the public but can also achieve a sustainable competitive advantage. The results show that companies that conduct business ethically tend to gain stronger customer loyalty, higher employee productivity, and mitigation of reputational risks. In addition, ethical business behavior also has a positive impact on the achievement of long-term goals and corporate sustainability. Therefore, ethical business behavior is not just a moral choice but also an effective business strategy in facing competition professionally